The use of pile columns during the building construction by the top-down method - Makhynia, O.; Halenko, Y. (Ways to Improve Construction Efficiency, 2023)
The article examines the analysis of publications regarding the use of various types of piles-columns during top-down construction. Today, the following types of piles can be used during construction using the "up-down" technology: bored piles, bored piles with a barrel extension (bell pile), barrettes (barrette), combined piles with a steel core (king post). The article analyzes the buildings that were built by the "up-down" method, as well as the structural characteristics of the piles-columns that were used during their construction. It was established that pile-columns are expected to absorb loads in a wide range from 1.5 to 44.5 MN, on average the calculated load is from 10 to 14 MN. The length of the piles varies from 16 to 67 m, on average - 30...35 m, and they were placed with steps from 1.8 to 4.3 m, on average - 3 m. A growing trend of using combined piles with a metal core (king post) was revealed. Their main advantage is the ability to immediately perceive significant loads from the above-ground part of the building during the simultaneous construction of its underground part and guaranteed indicators of strength and stability of the column. Installation of combined piles with a metal core (king post) involves two stages. At the first stage, a pit is arranged and a reinforcing frame is installed to it, then a concrete mixture is laid to the lower monolithic part of the pile, into which the steel core of the upper part is mounted and it is covered with gravel in the pit. At the second stage, during the construction of the underground floors, the metal core is concreted. At the same time, it was established that the installation and concreting of a metal body is a technologically complex and expensive process that requires a more detailed study of the possibility of improving structural and technological solutions and reducing the cost of work.